Faktor risiko kontaminasi telur cacing soil transmitted helminths pada sayur lalapan - Lilik Setyowatiningsih; Surati; Wikandari , Ririh Jatmi (Jurnal Kedokteran Universitas Palangka Raya, 2023)
Management process of fresh vegetables can indicate the incidence of Soil Transmitted Helminths (STH) infection in the community.The purpose of this study was to determine the risk factors that influence STH contamination in fresh vegetables from food stalls in Pedurungan District, Semarang. This type of research is descriptive using qualitative methods with cross sectional design. Based on the results of laboratory tests, a total of 165 samples examined found STH worm eggs with the species Trichuris trichiura (0.6%). Based on bivariate analysis, there was no significant relationship between education level, knowledge, personal hygiene and environmental sanitation to contamination of STH worm eggs in fresh vegetables in Semarang City.